The Influence of Transformational Leadership and Self-Sufficiency on Job Satisfaction and Employee Performance - Sutijah, Sutijah; Hidayati, Tetra; Ramadhani, Herry (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine the influence of transformational leadership and self-reliance on employee job satisfaction and performance. This study uses a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS) as the main analysis technique. The research population includes all employees, with purposive sampling used to select respondents who meet the research criteria. Data were collected through a structured questionnaire designed to measure transformational leadership, independence, job satisfaction, and employee performance. The findings show that transformational leadership has a significant and positive influence on job satisfaction and employee performance. Similarly, independence has a significant positive impact on job satisfaction and performance, indicating that employees who have greater self-confidence, autonomy, and independence tend to perform better and experience higher job satisfaction. Furthermore, job satisfaction acts as a mediating variable that strengthens the relationship between transformational leadership, autonomy, and performance outcomes. This highlights the importance of leaders who can inspire, motivate, and empower employees while fostering an independent and responsible work culture. The study concludes that developing transformational leadership practices and enhancing employee self-sufficiency are crucial strategies to improve organizational productivity and service quality in public institutions. The practical implications emphasize the need for managerial policies that promote supportive leadership behavior, employee empowerment, and continuous capability development to achieve optimal performance and sustainable organizational growth.